2020
DOI: 10.1016/j.jaapos.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus pandemic on pediatric eye-related emergency department services

Abstract: Literature describing the trends and utilization of pediatric eye-related emergency department (ED) visits is limited. We performed a retrospective cohort study of 311 pediatric patients visiting Bascom Palmer Eye Institute (BPEI) ED between March and May 2020 to quantify the effect of the coronavirus (COVID-19) on ophthalmology care utilization. In our study, pediatric ED visits declined by half at the onset of the pandemic in March. The number of visits reached the lowest point in early April and increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
2
11
0
1
Order By: Relevance
“…Compared to the average volume of visits performed in the same period in the previous three years, we experienced a drop of 79.4%. This finding is consistent with those reported by Shak et al, since they experienced a halving of the PEED consultations at their eye clinic during the first wave of the pandemic [ 6 ]. Conversely, our PEED has not direct access, so people have to stay in a shared waiting room before triaging and being sent to the Ophthalmic Unit.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the average volume of visits performed in the same period in the previous three years, we experienced a drop of 79.4%. This finding is consistent with those reported by Shak et al, since they experienced a halving of the PEED consultations at their eye clinic during the first wave of the pandemic [ 6 ]. Conversely, our PEED has not direct access, so people have to stay in a shared waiting room before triaging and being sent to the Ophthalmic Unit.…”
Section: Discussionsupporting
confidence: 92%
“…4 Despite this guidance, studies have shown that fewer patients with ophthalmic emergencies sought care during the initial months of the pandemic. 5,6 This is also reflected outside of ophthalmology by a decline in overall emergency department visits 7 and critical procedures performed. 8,9 Possible explanations include challenges posed by stay-at-home measures, socioeconomic hardship, and general anxiety brought about by the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…5 Possible reasons include fear of acquiring COVID-19 and stay-at-home orders. 2,6 Additionally there were fewer ocular traumas in 2020 compared to 2018 and 2019, possibly due to cancellation of sports activities. A similar trend was observed in Italy.…”
mentioning
confidence: 99%
“…Although studies have documented reductions in urgent ophthalmic referrals during the first pandemic wave, few have examined its effects on pediatric ophthalmology. 2,3 We sought to characterize the impact of the first COVID-19 wave on pediatric emergency ophthalmic consultations and surgeries performed at a pediatric tertiary care hospital in Montreal, Quebec, the province with the highest number of cases during the first-wave. 1 This study was approved by the McGill University Health Centre Institutional Review (17.9%) during 2020.…”
mentioning
confidence: 99%